Factors Associated With the Decline of C-Peptide in a Cohort of Young Children Diagnosed With Type 1 Diabetes - Steck, Andrea K; Liu, Xiang; Krischer, Jeffrey P; Haller, Michael J; Veijola, Riitta; Lundgren, Markus; Ahmed, Simi; Akolkar, Beena; Toppari, Jorma; Hagopian, William A; Rewers, Marian J; Elding Larsson, Helena (The journal of clinical endocrinology and metabolism, 2021)
Abstract Context Understanding factors involved in the rate of C-peptide decline is needed to tailor therapies for type 1 diabetes (T1D). Objective Evaluate factors associated with rate of C-peptide decline after a T1D diagnosis in young children. Design Observational study. Setting Academic centers. Participants A total of 57 participants from the Environmental Determinants of Diabetes in the Young (TEDDY) study who were enrolled at 3 months of age and followed until T1D, and 56 age-matched children diagnosed with T1D in the community. Intervention A mixed meal tolerance test was used to measure the area under the curve (AUC) C-peptide at 1, 3, 6, 12, and 24 months postdiagnosis. Outcome Factors associated with rate of C-peptide decline during the first 2 years postdiagnosis were evaluated using mixed effects models, adjusting for age at diagnosis and baseline C-peptide. Results Adjusted slopes of AUC C-peptide decline did not differ between TEDDY subjects and community controls (P = 0.21), although the former had higher C-peptide baseline levels. In univariate analyses combining both groups (n = 113), younger age, higher weight and body mass index z-scores, female sex, an increased number increased number of islet autoantibodies, and IA-2A or ZnT8A positivity at baseline were associated with a higher rate of C-peptide loss. Younger age, female sex, and higher weight z-score remained significant in multivariate analysis (all P < 0.02). At 3 months after diagnosis, higher HbA1c became an additional independent factor associated with a higher rate of C-peptide decline (P < 0.01). Conclusion Younger age at diagnosis, female sex, higher weight z-score, and HbA1c were associated with a higher rate of C-peptide decline after T1D diagnosis in young children.